2019
DOI: 10.1111/scd.12358
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of nanomicelle curcumin in the prevention of radiotherapy‐induced mucositis in head and neck cancers

Abstract: Oral mucositis (OM) is a complication of head and neck cancer (HNC) therapy with negative impact on the quality of life. Although definitive treatment has not yet been established, there is interest towards the use of natural compounds owing to their few side effects. Curcumin has a variety of biological and pharmacological properties including anticancer and anti‐inflammatory effects. Aim The aim of this study is to evaluate the effect of curcumin in the form of nanomicelle on OM in HNC patients receiving rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 35 publications
1
70
0
1
Order By: Relevance
“…Seven randomized controlled trials (Rao et al, 2014, Mansourian et al, 2015, Patil et al, 2015, Charanthimath, 2016, Delavarian et al, 2019, Arun et al, 2020, Shah et al, 2021 non randomised controlled trials (Adhvaryu et al, 2018, Saldanha andAlmeida, 2014) investigated the efficacy/effects of curcumin in oral mucositis. Evaluation period varied from 5 days to 8 weeks, follow up visits were 5 days (Saldanha and Almeida, 2014), 2 weeks (Charanthimath, 2016), 20 days (Patil et al, 2015), 42 OR (("head" "[All Fields] AND "neck" "[All Fields] AND "cancer" "[All Fields] or "head and neck cancer" OR "Head and Neck Neoplasms"[MeSH Terms])AND (("stomatitis"[MeSH Terms} OR "stomatitis[All Fields] OR ("oral" [All Fields]AND "mucositis" [All Fields])) OR "oral mucositis:[All Fields].…”
Section: Study Design and Duration Of Included Studiesmentioning
confidence: 99%
“…Seven randomized controlled trials (Rao et al, 2014, Mansourian et al, 2015, Patil et al, 2015, Charanthimath, 2016, Delavarian et al, 2019, Arun et al, 2020, Shah et al, 2021 non randomised controlled trials (Adhvaryu et al, 2018, Saldanha andAlmeida, 2014) investigated the efficacy/effects of curcumin in oral mucositis. Evaluation period varied from 5 days to 8 weeks, follow up visits were 5 days (Saldanha and Almeida, 2014), 2 weeks (Charanthimath, 2016), 20 days (Patil et al, 2015), 42 OR (("head" "[All Fields] AND "neck" "[All Fields] AND "cancer" "[All Fields] or "head and neck cancer" OR "Head and Neck Neoplasms"[MeSH Terms])AND (("stomatitis"[MeSH Terms} OR "stomatitis[All Fields] OR ("oral" [All Fields]AND "mucositis" [All Fields])) OR "oral mucositis:[All Fields].…”
Section: Study Design and Duration Of Included Studiesmentioning
confidence: 99%
“…The effect of nanocurcumin on oral mucositis in patients with head and neck cancer who are receiving radiotherapy was assessed (Delavarian et al., 2019). The severity of oral mucositis was found to significantly decrease in the treatment group compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Adverse events reported after the use of nanopolyphenols in the included studies were minimal. Of the 18 studies that provided this information, a total of 12 studies reported no adverse effects during or after treatment (Abdolahi et al., 2018; Afshar et al., 2020; Alizadeh et al., 2018; Amorndoljai et al., 2017; Delavarian et al., 2019; Dolati, Aghebati‐Maleki et al., 2018; Farhadi et al., 2018; Gallelli et al., 2020; Hashemzadeh et al., 2020; Javadi et al., 2019; Parohan et al., 2019; Sasaki et al., 2011). Mild adverse events reported include stomachache (Asadi et al., 2019; Asadi, Gholami, Siassi, Qorbani et al., 2019) and nausea (Jazayeri‐Tehrani et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Outrossim, encontrou-se 4 trabalhos aplicando curcumina em cápsulas, colutório e agente fotossensibilizante na terapia fotodinâmica no combate a MO durante o tratamento de câncer, e em todos o resultado foi de retardamento do início das lesões, bem como redução da gravidade e melhora no estado geral de saúde (Delavarian et. al, 2019;Pinheiro et.…”
Section: Discussionunclassified